2016
DOI: 10.1002/mrm.26090
|View full text |Cite
|
Sign up to set email alerts
|

A fast and flexible MRI system for the study of dynamic vocal tract shaping

Abstract: Purpose To develop and evaluate a MRI-based system for study of dynamic vocal tract shaping during speech production, which provides high spatial and temporal resolution. Methods The proposed system utilizes (a) custom eight-channel upper airway coils that have high sensitivity to upper airway regions of interest, (b) 2D golden angle spiral gradient echo acquisition, (c) on-the-fly view-sharing reconstruction, and (d) off-line temporal finite difference constrained reconstruction. The system also provides si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
145
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(145 citation statements)
references
References 54 publications
0
145
0
Order By: Relevance
“…Motion artifacts exist in some of the current results. This is not surprising as Lingala et al pointed out that fully sampled single slice RT‐MRI cannot resolve all tongue movements, especially during faster pace speaking or those involving intrinsically faster subsystem movement such as by the tongue tip. These artifacts can be mitigated by under‐sampling and constrained reconstruction methods, which have yet to be explored in combination with tagging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion artifacts exist in some of the current results. This is not surprising as Lingala et al pointed out that fully sampled single slice RT‐MRI cannot resolve all tongue movements, especially during faster pace speaking or those involving intrinsically faster subsystem movement such as by the tongue tip. These artifacts can be mitigated by under‐sampling and constrained reconstruction methods, which have yet to be explored in combination with tagging.…”
Section: Discussionmentioning
confidence: 99%
“…Markl et al suggested a CNR threshold of 6 for cardiac applications. Simulated σ is calculated as the simulated steady state signal divided by 15, as suggested by previous experiments . A threshold time can be calculated as the time span between the tag being placed and when the CNR decrease below the threshold value.…”
Section: Methodsmentioning
confidence: 99%
“…By the end of the weekend, we had counted 10 Kens and 13 Georges." With recent developments in imaging technology (Lingala et al, 2016), it is possible to detect vocal fold abduction, even in the sagittal slice, of images acquired at an extremely high frame rate, allowing for use of segments that differ only in voicing.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this signal, time locked with the consonantal gestures, arises due to rtMRI scanner noise resonating in the speaker's vocal tract. In order to ensure that these articulations are, indeed, produced without any phonation and are not whispered, utilization of the imaging technique described above (Lingala et al, 2016) to determine if sustained adduction or abduction of the vocal folds are observed at the appropriate points in time or collection of oral airflow data would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Speech responses were acquired using an rtMRI protocol developed specifically for the dynamic study of upper airway movements [22,23]. Experiments were performed on a GE Signa Excite 1.5T scanner with a custom eight-channel upper airway receiver coil.…”
Section: Stimuli Data Acquisition and Analysismentioning
confidence: 99%